Characterization of chondroitin sulfate from deer tip antler and osteogenic properties - Peraphan Pothacharoen (2018)
Deer antler is a highly regenerative tissue that involves cellular differentiation, osteogenesis and ossification processes. Chondroitin sulfate is the major glycosaminoglycan contained in antler connective tissue and has been isolated from cartilaginous antler by 4 M GuHCl extraction, gradient ultracentrifugation and chromatography techniques. We examined the disaccharide composition by 2-AB labeling and anion exchange HPLC analysis of the three resultant fractions (high, medium and low density fractions). The high density fraction consists of A-unit and D-unit disaccharide in the ratio of 1:1, whereas, the CS disaccharide composition ratio of A-unit:C-unit:D-Unit:E-unit contained in medium and low density fractions are 3:4:3:1 and 2:2:2:1, respectively. The only intact CS oligosaccharides of the medium density fraction upregulated gene expression of bone-specific proteins of a human osteoblastic cell line (hFOB1.19). Thus, CS oligosaccharides from cartilaginous deer antler, with their oversulfated chondroitin sulfate composition, demonstrated the physiological properties and may be good candidates for osteogenetic agents in humans. © Springer Science+Business Media, LLC 2011.